Chiropractic international research collaborative (CIRCuit): the development of a new practice-based research network, including the demographics, practice, and clinical management characteristics of clinician participants - Kenneth J Young; Sasha Aspinall; Silvano Mior; Jordan Gliedt; Joseph Spencer; Christoffer Børsheim; Jennifer Nash; Melinda Ricci; Jonathan Shurr; Iben Axén (Chiropractic & Manual Therapies)
Abstract Objectives To describe the structure and development of a new international, chiropractic, practice-based research network (PBRN), the Chiropractic International Research Collaborative (CIRCuit), as well as the demographic, practice, and clinical management characteristics of its clinician participants. An electronic survey was used to collect information on their demographics, practice, and clinical management characteristics from clinicians from 17 October through 28 November 2022. Descriptive statistics were used to report the results. Background PBRNs are an increasingly popular way of facilitating clinic-based studies. They provide the opportunity to collaboratively develop research projects involving researchers, clinicians, patients and support groups. We are unaware of any international PBRNs, or any that have a steering group comprised of equal numbers of clinicians representing the different international regions. Results 77 chiropractors responded to the survey (0.7% of EBCN-FB members). 48 were men (62%), 29 women (38%). Thirty-six (47%) were in North America, 18 (23%) in Europe, and 15 (19%) in Oceania. Participants reported predominantly treating musculoskeletal issues, often with high-velocity, low-amplitude spinal manipulation (95%), but also with soft tissue therapy (95%), exercise (95%), and other home care (up to 100%). Methods The development of CIRCuit is described narratively. Members of the Evidence-Based Chiropractic Network Facebook group (EBCN-FB) were invited to become clinician participants by participating in the survey. Conclusions This paper describes the development of a new PBRN for chiropractors. It offers a unique opportunity to facilitate the engagement of clinical chiropractors with research, as well as for academics to readily be able to access an international cohort of clinicians to collaboratively develop and conduct research. Although the results of the survey are not statistically generalisable, the initial cohort of CIRCuit clinician participants use similar techniques on similar types of conditions as the profession at large. The international structure is unique among PBRNs and offers the opportunity to help develop innovative research projects.